2015
DOI: 10.1159/000437330
|View full text |Cite
|
Sign up to set email alerts
|

TNFAIP2 Inhibits Early TNFa-Induced NF-κB Signaling and Decreases Survival in Septic Shock Patients

Abstract: (IL)-8. The minor G allele of TNFAIP2 rs8126 resulted in greater TNFAIP2 expression, decreased IL-8 production and was associated with decreased survival in patients experiencing septic shock. These data suggest that TNFAIP2 is a novel inhibitor of NF-κB that acts as an autoinhibitor of the TNFα response during septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
(41 reference statements)
0
19
0
Order By: Relevance
“…In VSMC module 31 we identified 14 genes ( APOLD1, MT1A, ZFP36, EGR1, JUNB, FOSB, JUN, FOS, RERGL, MT1M, DNAJB1, CCNH, HSPA1B and HSPA1A ) whose expression was significantly upregulated in PA cells and with strong network connectivity. Among these genes we identify immediate-early (IE) genes ZFP36, EGR1, JUNB, FOSB and FOS as critical response genes in this hallmark process which cluster tightly together and correlate with NFKBIA and TNFAIP2 - both inhibitors of NFkB-mediated signaling 58 (Extended Data Fig. 6c).…”
Section: Resultsmentioning
confidence: 99%
“…In VSMC module 31 we identified 14 genes ( APOLD1, MT1A, ZFP36, EGR1, JUNB, FOSB, JUN, FOS, RERGL, MT1M, DNAJB1, CCNH, HSPA1B and HSPA1A ) whose expression was significantly upregulated in PA cells and with strong network connectivity. Among these genes we identify immediate-early (IE) genes ZFP36, EGR1, JUNB, FOSB and FOS as critical response genes in this hallmark process which cluster tightly together and correlate with NFKBIA and TNFAIP2 - both inhibitors of NFkB-mediated signaling 58 (Extended Data Fig. 6c).…”
Section: Resultsmentioning
confidence: 99%
“…IGF2 is present in follicular fluid and has recently been shown to promote malignant transformation in immortalized TE cell lines (Hsu et al, 2019). TNFAIP2 is thought to be involved in inflammatory angiogenesis and has been reported to down regulate NF-κB (Jia et al, 2018;Thair et al, 2015). If we suppose TNFAIP2 has a role in controlling NF-κB signaling in the TE, we would expect to see NF-κB signaling activity to be reduced in the proximal TE.…”
Section: Discussionmentioning
confidence: 99%
“…16 In vitro experiments, TNFAIP2 used to be differentially expressed in blood vessels, and it maybe an inhibitor of NF-κB or an auto-inhibitor of TNF-α response. 17 TNFAIP2 can also serve as a target gene for retinoic acid and play an important role in inducing apoptosis in acute promyelocytic leukemia and multiple tumors. 18 Some studies have demonstrated that TNFAIP2 can regulate inflammation and angiogenesis, induce apoptosis, promote cell proliferation, adhesion, migration and invasion, and mediate the formation of membrane nanotubes by NF-κB signaling pathway, Retinoic acid signaling pathway and Kruppel-like factor 5 (KLF5) signaling pathway.…”
Section: Physiological Functions and Mechanisms Of Tnfaip2mentioning
confidence: 99%